Interface and defect structures in YBa(2)Cu(3)O(7-delta) and Nb : SrTiO(3) heterojunction - Fu, Lian-feng; Browning, Nigel D.; Ramadan, W.; Ogale, Satishchandra B.; Kundaliya, D. C.; Venkatesan, T. (Journal of Physics D-Applied Physics, 2007)
YBa(2)Cu(3)O(7-delta) thin films grown on a Nb-doped SrTiO(3) substrate by a pulsed laser deposition method have been fully characterized by scanning transmission electron microscopy Z- contrast imaging and electron energy loss spectroscopy techniques. The Nb distribution was found to be uniform and unchanged across the interface, ensuring a high quality p - n junction heterointerface. We first observed the coexistence of 124 and 125 YBCO defect structure phases, appearing as planar defects in a YBCO thin film. Dispersive Y(2)O(3) nanoparticles have also been observed in the thin film. The interaction of these defect structures and Y(2)O(3) nanoparticles is thought to be beneficial for pinning flux through the entire film thickness.